Does postoperative pulmonary infection correlate with intestinal flora following gastric cancer surgery? — a nested case–control study - Yang, Jie; He, Yuhua; Liao, Xi; Hu, Jiankun; Li, Ka (Frontiers in Microbiology, 2023)
The primary objective of this study was to investigate the potential correlation between gut microbes and postoperative pulmonary infection in gastric cancer patients. Additionally, we aimed to deduce the mechanism of differential functional genes in disease progression to gain a better understanding of the underlying pathophysiology. A nested case‒control study design was utilized to enroll patients with gastric cancer scheduled for surgery at West China Hospital of Sichuan University. Patients were categorized into two groups, namely, the pulmonary infection group and the control group, based on the development of postoperative pulmonary infection. Both groups were subjected to identical perioperative management protocols. Fecal samples were collected 24 hours postoperatively and upon pulmonary infection diagnosis, along with matched controls. The collected samples were subjected to 16S rDNA and metagenomic analyses, and clinical data and blood samples were obtained for further analysis. A total of 180 fecal specimens were collected from 30 patients in both the pulmonary infection and control groups for 16S rDNA analysis, and 3 fecal samples from each group were selected for metagenomic analysis. The study revealed significant alterations in the functional genes of the intestinal microbiome in patients with postoperative pulmonary infection in gastric cancer, primarily involving Klebsiella, Enterobacter, Ruminococcus, and Collinsella. During postoperative pulmonary infection, gut flora and inflammatory factors were found to be associated with the lipopolysaccharide synthesis pathway and short-chain fatty acid (SCFA) synthesis pathway. The study identified enriched populations of Klebsiella, Escherella, and intestinal bacteria during pulmonary infection following gastric cancer surgery. These bacteria were found to regulate the lipopolysaccharide synthesis pathway, contributing to the initiation and progression of pulmonary infections. Inflammation modulation in patients with postoperative pulmonary infection may be mediated by short-chain fatty acids. The study also revealed that SCFA synthesis pathways were disrupted, affecting inflammation-related immunosuppression pathways. By controlling and maintaining intestinal barrier function, SCFAs may potentially reduce the occurrence of pulmonary infections after gastric cancer surgery. These findings suggest that targeting the gut microbiome and SCFA synthesis pathways may be a promising approach for preventing postoperative pulmonary infections in gastric cancer patients.